Sensation seeking and spatial ability in athletes: An evolutionary account - Hromatko, Ivana (Array, 2009)
The aim of this study was threefold: (a) to examine sex differences in sensation seeking and spatial abilities in a sample of athlete students, (b) to explore whether measures of sensation seeking and spatial ability can be used to distinguish between athletes engaging in sports of different levels of risk, and (c) to explore the relationship between sensation seeking and spatial abilities in a sample of athlete students. A total of 201 students athletes engaged in sports of different levels of risk completed the Spatial relations test, Mental rotation test, and Zuckerman's Sensation Seeking Scale-V. Men scored higher than women in both measures of spatial abilities and on DIS, while women scored higher than men on ES. High-risk group had higher SSS and TAS scores than low- and medium- risk groups, and low-risk group had lower DIS scores than medium- and high-risk group, but there were no differences in spatial ability among athletes engaged in sports of different levels of risk. Spatial ability correlated with sensation seeking measures in men only. The results are discussed in terms of possible common biological background of these two sex-dimorphic traits.